The homilies of John Chrysostom on 1 Corinthians 12 : a model of Antiochene exegesis on the charismata - De Wet, Chris Len (University of Pretoria, 2013)
The impetus of this study is that by understanding the way John Chrysostom (flor. 398 AD) interprets the gifts of the Spirit (Charismata) as an Antiochene exegete, insights may be yielded as to how the general tendency of Antiochene exegetes may aid in the interpretation of 1 Corinthians 12:1-13:3, which in turn also contributes to the current research on the New Testament. This study asks the question: How does John Chrysostom, as typical Antiochene exegete, interpret the charismata? In order to address this problem, an inductive-deductive method is followed, in which the general characteristics of the Antiochene exegetical school will be examined and then an analysis of the homilies of John Chrysostom, specifically his corpus Homilies on 1 Corinthians, homily 29 to 32, is given. Each homily is examined in the light of its contents, with specific reference to certain traits typical of Antiochene exegesis, such as sensitivity to history, social- and cultural customs, as well as to the grammar and rhetoric of, in this instance, Paul the Apostle. A translation of each homily is also provided. Finally, their value for current research is expounded. Each homily is translated and evaluated from the basis of the ancient Greek text, in which the homilies were originally composed. The homilies are also evaluated in the light of primary and secondary sources as inter-texts. Since the homilies are verbal commentaries, early Christian literature (of approximately 100-700 AD) on the same topic, the primary sources, are compared with the homilies of Chrysostom. Other ancient sources, not necessarily Christian, of the same period or earlier are also incorporated. But it is also necessary to view the homilies within the context of modern commentaries. Thus, a number of modern secondary sources are also evaluated in the light of the homilies and vice versa. In conclusion, the homilies depict an insightful image on how the Antiochene exegetical school viewed the charismata, which in turn, also provides valuable insights for modern interpreters. In this study of the Wirkungsgeschichte of 1 Corinthians 12:1-13:3, one is reminded that, although these primary sources are dated, they are still unexpendable resources for the current study of 1 Corinthians and of the New Testament in general. === Dissertation (MA (Ancient Languages and Cultures Studies))--University of Pretoria, 2007. === Ancient Languages === unrestricted